Conjugate Eye Deviation on CT Associated With Worse Outcomes Despite IV Thrombolysis. (April 2017) - Shah, Nirav H.; Bhatt, Nirav; Tipirneni, Anita; Condes, Diego; Khandelwal, Priyank; Romano, Jose G.
Introduction: Rapid stroke management has significant implications in patient outcomes. Ipsilateral computed tomography conjugate eye deviation (CT-CED) has been associated with worse outcomes but has never been evaluated as predictive of vascular occlusion. To test the hypothesis that CT-CED is a marker for vascular occlusion, we evaluated patients treated with intravenous tissue plasminogen activator (IV tPA). Methods: We performed a retrospective analysis of patients with acute ischemic stroke treated with IV tPA at a large tertiary care hospital over an 18-month period. A waiver of informed consent was granted. Two examiners evaluated baseline brain CTs blinded to the location of infarct to assess the presence of CT-CED and follow-up imaging for the location of infarct and the presence of intracranial large vessel occlusion. Demographics, initial National Institutes of Health Stroke Scale (NIHSS), modified Rankin Scales (mRSs), and hospital length of stay (LOS) were collected. Results: Among 104 patients treated with IV tPA, 36 had CT-CED. Inter-rater reliability for CT-CED was excellent (κ = 0.97; 95% confidence interval: 0.98-1.0). The CT-CED group was older (69.8 vs 64 years; P = .038), had higher initial NIHSS (14.6 vs 11; P = .01), worse mRS (3.2 vs 2.4; P = .03), and longer LOS (8.4 vs 6.4; P = .05) compared with those without CT-CED. A vascular occlusion in the territory of the infarct was seen in 58% of patients with CT-CED versus 32% without CT-CED ( P < .01). Atrial fibrillation (AF) was diagnosed in 61% patients with CT-CED versus 22% without ( P < .01). Conclusion: The CT-CED is associated with higher initial NIHSS, large vessel occlusion, and AF. Prospective studies are needed to ascertain whether CT-CED may be utilized part of a screen for endovascular therapy.